Relationship between recovery of motor function and neuropsychological functioning in cerebral infarction patients: the importance of social functioning in motor recovery - Min Cheol Chang, Sung-Won Park, Byung-Joo Lee, Donghwi Park (Journal of Integrative Neuroscience, 2020)
Impaired motor function is a common disabling sequela after stroke. It is closely associated with the patient’s quality of life and independence. Neuropsychological dysfunctions also frequently occur in stroke patients. In this paper, we evaluate the relationship between the recovery of motor function and neuropsychological functions, including cognition, language, emotion, behavior, personality, and social interaction, to provide appropriate and effective therapy for stroke patients. Motor function, neuropsychological status, social functioning, as well as emotional aspects such as depression and anxiety symptoms, were initially evaluated one month after cerebral infarction onset. The evaluations were repeated three months after the onset. Motor function was assessed with the Modified Barthel Index. The neuropsychological status was evaluated using the Mini-Mental State Examination, Global Deterioration Scale, digit span test, Korean-Boston Naming Test, Vineland Social Maturity Scale, Neuropsychiatric Inventory, Beck’s Depression Inventory, and Beck Anxiety Inventory. In the results, the Modified Barthel Index, Mini-Mental State Examination, Global Deterioration Scale, digit span test, and Vineland Social Maturity Scale were significantly different between the two-time points (P< 0.05). Initial Social Maturity Scale Social Age and Social Maturity Scale Social Quotient categories of the Vineland Social Maturity Scale and Mini-Mental State Examination scores were significantly correlated with Modified Barthel Index improvement (P< 0.05). The amount of change in the Social Maturity Scale Social Age and Social Maturity Scale Social Quotient scores was significantly correlated with Modified Barthel Index improvement (P< 0.05). In multiple linear regression analysis, only the initial Social Maturity Scale Social Quotient score and the amount of score change in Social Maturity Scale Social Quotient showed a significant correlation with Modified Barthel Index improvement (P< 0.05). Social function and interaction are important in motor recovery of ischemic stroke patients.